POLA TINDAKAN GURU DALAM MENDIDIK ANAK PENYANDANG ADHD DI SD ISLAM PERMATA MOJOSARI - Ocmy Krisania Tauhida, Ocmy; Farid Pribadi, Farid (Universitas Pendidikan Nasional, 2022)
People with ADHD are free to pursue their education, in both inclusive and regular schools with adequate facilities. In reality, some schools accept ADHD without consideration, especially the Permata Mojosari Islamic Elementary School which is a new school. The purpose of the study was to analyze the pattern of action teachers and ADHD students in regular schools. The research method uses qualitative ethnomethodology theory by Harold Garfinkel. The analysis technique uses ethnographic methods. The research subjects were ADHD students and teachers at the elementary school through observation, interviews, and documentation. The results are, first, ADHD students follow the lesson like normal students, but their seats are close to the teacher. Second, students provide special understanding. Third, students think about solving questions. Fourth, the teacher helps write the spelling based on the students' answers. Fifth, the writing is in his book. Sixth, when students are bored, they are given knick-knacking therapy. Seventh, when students succeed in carrying out the instructions correctly, a reward is given, when it violates social norms, punishment is given. The pattern of action in Garfinkel's ethnomethodology is influenced by the ability of the teacher.